2002
DOI: 10.1007/bf02946701
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of mycotoxins and mycoflora of argentinien popcorn

Abstract: Argentina is the first popcorn exporting country worldwide. In 1997-1998 harvest season, 40,000 ha were sown with a production of 125,000 tons; 120,000 tons of this production were exported to more than 40 countries. The objectives of this study were to isolate and to identify the fungi present in this cereal and to assess the occurrence of mycotoxins in freshly harvested popcorn in Buenos Aires province, Argentina, in 1999. All popcorn samples showed fungal contamination. A total of 4,211 isolates were recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
2
1
Order By: Relevance
“…The data on dominant fungal species on maize grains in Serbia are similar to those previously described worldwide (Abdel-Mallek et al, 1993;Mubatanhema et al, 1999;Hussein et al, 2002;Pacin et al, 2002;Logrieco et al, 2003;Somda et al, 2008;Ramos et al, 2010). However, when comparing the data on the incidence of mycobiota on maize seeds obtained and presented in this study with previously published results by Lević et al (1997) it can be deduced that the incidence of F. graminearum, F. oxysporum, F. subglutinans and F. verticillioides has changed over last 15 years.…”
Section: Discussionsupporting
confidence: 83%
“…The data on dominant fungal species on maize grains in Serbia are similar to those previously described worldwide (Abdel-Mallek et al, 1993;Mubatanhema et al, 1999;Hussein et al, 2002;Pacin et al, 2002;Logrieco et al, 2003;Somda et al, 2008;Ramos et al, 2010). However, when comparing the data on the incidence of mycobiota on maize seeds obtained and presented in this study with previously published results by Lević et al (1997) it can be deduced that the incidence of F. graminearum, F. oxysporum, F. subglutinans and F. verticillioides has changed over last 15 years.…”
Section: Discussionsupporting
confidence: 83%
“…The absence of DON in popcorn has already been mentioned in Portugal in 2008 by the analysis of 49 samples by TLC (Martins et al, 2008). Similar results were obtained by Pacin et al (2002) in Argentina through the analysis of 42 popcorn samples. However, in Brazil, a study with 105 popcorn samples reported DON in four samples with levels ranging from 32 to 40 mg/kg (Oliveira et al, 2001).…”
Section: Analysis Of Mycotoxins In Unpopped and Popped Popcornsupporting
confidence: 88%
“…The levels of LOQ are lower than the maximum residue limits established by EU for these mycotoxins (Commission Regulation N 1126/2007. Furthermore, the LOQ of DON was better than those obtained by Oliveira, Soares, and Sawazaki (2001) 150 mg/kg, Pacin et al (2002) 125 mg/kg and Martins, Almeida, Marques, and Guerra (2008) 100 mg/kg. Better LOQ were also obtained for ZON when compared to those obtained by Pacin et al (2002) 125 mg/kg.…”
Section: Limit Of Detection (Lod) and Limit Of Quantification (Loq)contrasting
confidence: 49%
“…Of the two species identified here, F. verticillioides was consistently found both on the seed surface and within the internal tissues (Figure a). This species is the most frequently isolated species from maize seeds in other regions of world, for example, Argentina (Pacin et al., ), Mexico (Leyva‐Madrigal et al., ), and Serbia (Lević et al., ), and systematically infects all parts of plants (Oren et al., ). Isolates of F. verticillioides have also been demonstrated to be highly aggressive and capable of co‐infecting with other species of Fusarium (Leyva‐Madrigal et al., ).…”
Section: Discussionmentioning
confidence: 99%